2019
DOI: 10.1002/jwmg.21646
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and tick parasitism in birds of coastal southeastern Virginia

Abstract: One of North America's major avian migratory pathways occurs along a large anthropogenically modified coastal region of southeastern Virginia, USA. Because hundreds of avian species migrate along the east coast of North America, understanding factors affecting birds and their health is of ecological and conservation interest. Within southeastern Virginia, 14 tick species have been documented, all of which may serve as vectors of vertebrate pathogens. We tested 5 hypotheses to understand how varying levels of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 64 publications
(79 reference statements)
1
1
0
Order By: Relevance
“…Unlike prevalence of tick infestation, intensity of infestation was unrelated to urbanization. Previous studies show a link between large-scale land use and ticks, hosts, and pathogens (Allan et al 2003;LoGiudice et al 2003;Heller et al 2019). Our results suggest that even if the proportion of birds carrying at least one tick is influenced by urbanization, numbers of ticks carried by infested birds can be more consistent across an urban-to-rural gradient.…”
Section: Tick Infestation Of Birds Relative To Urbanization Intensitysupporting
confidence: 51%
See 1 more Smart Citation
“…Unlike prevalence of tick infestation, intensity of infestation was unrelated to urbanization. Previous studies show a link between large-scale land use and ticks, hosts, and pathogens (Allan et al 2003;LoGiudice et al 2003;Heller et al 2019). Our results suggest that even if the proportion of birds carrying at least one tick is influenced by urbanization, numbers of ticks carried by infested birds can be more consistent across an urban-to-rural gradient.…”
Section: Tick Infestation Of Birds Relative To Urbanization Intensitysupporting
confidence: 51%
“…A study in the eastern U.S. found that birds in areas with extensive impervious surface (i.e. more urbanized areas) and water bodies were less likely to carry ticks, but percent imperviousness alone did not predict infestation (Heller et al 2019). Pathogen prevalence in ticks carried by birds may also vary in relation to urbanization, as indicated by a study showing urban birds are less likely to carry B. burgdorferi-infected ticks (Hamer et al 2012b).…”
Section: Introductionmentioning
confidence: 99%